2022
DOI: 10.1021/acs.est.2c01079
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Embryonic Metformin Exposure on Wild and Laboratory-Spawned Fathead Minnow (Pimephales promelas) Populations

Abstract: Metformin is routinely detected in aquatic ecosystems because of its widespread use as a treatment for Type 2 diabetes. Laboratory studies have shown that exposure to environmentally relevant concentrations of metformin can alter metabolic pathways and impact the growth of early life stage (ELS) fish; however, it is unknown whether these effects occur in wild populations. Herein, we evaluate whether findings from laboratory studies are representative and describe the relative sensitivities of both populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…For example, 28-day and 57-day MET exposures at concentrations of 1–100 μg/L and 1 μg/L have been shown to induce decreased weight and length in the early life stages of the Japanese medaka ( Oryzias latipes ) and S. trutta , respectively. Yet, an increase in length or no effects on growth parameters were observed when embryos/larvae of fathead minnow ( P. promelas) were exposed to similar MET concentrations for 5 or 21 days, respectively. A similar increase in length was reported for P. promelas larvae exposed to 31 μg/L MET at day 30 and an increase in the condition factor after MET exposure of 322 μg/L at day 64 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 28-day and 57-day MET exposures at concentrations of 1–100 μg/L and 1 μg/L have been shown to induce decreased weight and length in the early life stages of the Japanese medaka ( Oryzias latipes ) and S. trutta , respectively. Yet, an increase in length or no effects on growth parameters were observed when embryos/larvae of fathead minnow ( P. promelas) were exposed to similar MET concentrations for 5 or 21 days, respectively. A similar increase in length was reported for P. promelas larvae exposed to 31 μg/L MET at day 30 and an increase in the condition factor after MET exposure of 322 μg/L at day 64 …”
Section: Resultsmentioning
confidence: 99%
“…Apart from the present work, there is a paucity of data assessing long-term effects of environmentally relevant concentrations of MET in different time-points during the fish life cycle. Most of the studies available tested MET concentrations above those reported in surface waters, and/or fish were exposed for short time periods, covering only one stage of the life cycle. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…However, several works performed by distinct institutions using different fish species point mostly to negative effects at ranges from nanograms per liter to low micrograms per liter. Thus, even if some contrasting findings were reported by different teams for fathead minnows ( Pimephales promelas ), with the latest study by Nielsen et al showing the impact on embryonic development at 5 μg/L, particularly in wild-spawned fathead minnows, most studies support effects in the range of environmental concentrations. The reported effects include the disruption of embryonic development in zebrafish and fathead minnows at concentrations as low as 0.39–5 μg/L; vitellogenin (VTG) induction and disruption of reproduction-associated signaling pathways in fathead minnows, zebrafish, and Japanese rice fish ( Oryzias latipes ) at concentrations ranging from 0.39 to 40 μg/L; and changes in the metabolism of lifelong-exposed zebrafish and in processes related to the cell cycle, DNA repair, and steroid hormone biosynthesis, concomitantly to alterations in apical end points such as growth, hepatosomatic index, and fertilization rate , at concentrations ranging from 0.39 to 14.4 μg/L.…”
Section: An Underestimated Riskmentioning
confidence: 93%
“…In another interesting study on metformin, Nielsen et al found that exposure to metformin during development has a more harmful effect on wild fish larvae compared to those raised under laboratory conditions, suggesting reduced representativeness of lab studies. 161 Physiologically based kinetic (PBK) models, which offer a mechanistic understanding of how chemicals affect organisms, are crucial risk assessment tools but are limited to a few fish species and rarely account for the ionization of many pharmaceuticals. A study by Wang et al introduced a generalized PBK model for fish, estimating parameters based on fish and chemical properties, and enhancing its applicability across various species.…”
Section: Analyticalmentioning
confidence: 99%